Teacher Competency Development Through Optimization of Digital-Based Learning at SMPN 1 Baregbeg - Rahadian, Dian; Wasiyat, Raji; Yusup, Firman (Fakultas Kewirausahaan Universitas Garut, 2024)
This community service program aims to enhance the competencies of teachers at SMPN 1 Baregbeg through the optimization of digital-based learning. The initiative responds to the growing demand for teachers to master educational technology in line with digital-era requirements and modern curriculum implementation. The method included needs analysis, planning, training implementation, mentoring, and evaluation. The training focused on utilizing digital platforms, creating interactive learning media, and applying technology-based evaluation strategies. The results indicate a significant improvement in teachers’ digital skills and pedagogical competence, which positively impacted teaching effectiveness and student motivation. Challenges identified include teachers’ initial limited understanding of technology and the need for continuous development. This program highlights the importance of collaboration and ongoing training to support digital learning transformation in schools.